Analisis Strategi Komisi Penyiaran Indonesia Konten Televisi Edisi Ramadan - Purwanto Purwanto; Retno Sumarni; Solimin Solimin (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2022)
This study intends to illustrate how tv settings were in the period. The tests used in this study are subjective enlightenment methodologies, information collected as encounters, perceptions, documentation and investigation of specific information using information reduction (reduced information), information (display) and decision making (end of information). The consequences of this study must be seen from the depiction through perception, documentation and meetings with respondents, the approach taken by the Indonesian Broadcasting Commission on TV content during the long stretch of Ramadan.